2011
DOI: 10.1166/jnn.2011.3849
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Tribological and Mechanical Properties of Nanocomposites of Polyurethane/Poly(vinyl acetate)/CaCO<SUB>3</SUB>

Abstract: Properties of samples containing polyurethane (PU), poly(vinyl acetate) (PVAc) and nanosize particles of calcium carbonate (CaCO3) are correlated with concentrations of these components. Interphase phenomena in PU/PVAc/CaCO3 nanohybrids have been studied before, we focus here on wear and scratch resistance. In addition to polymer blends containing CaCO3, the effects of adding CaCO3 with grafted PVAc, and CaCO3 with grafted silane and PVAc in varying ratios are also evaluated. For blends that do not contain the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 8 publications
3
49
0
Order By: Relevance
“…The bumps model has been advanced before [23] and later confirmed in several cases [24,25] . Without the filler, the nominal contact area is equal to the real contact area.…”
Section: Frictionmentioning
confidence: 92%
“…The bumps model has been advanced before [23] and later confirmed in several cases [24,25] . Without the filler, the nominal contact area is equal to the real contact area.…”
Section: Frictionmentioning
confidence: 92%
“…The wear border made the movement of the ball more difficult at high loading condition (see Fig. 6) and in this situation the indenter had moved across the entire surface of each region [19]. The indenter is not just jumping from bump to bump, as it was doing with little contact with the surface between the bumps.…”
Section: Friction Coefficient and Wear Ratementioning
confidence: 99%
“…The change in H/E may have important implications for tribological applications where performance often is correlated with parameters such as H/E and H 3 /E 2 , with higher H 3 /E 2 commonly resulting in a higher load for non-elastic deformation, and higher wear resistance to wear as has been achieved by cross-linking ultra-high molecular weight polyethylene (UHMWPE) for replacement of hip prostheses. 37 The tribology and wear of polymers and polymer-based composites is complicated by viscoelastic recovery and brittleness, [38][39][40] with Brostow and co-workers reporting a direct correlation between a brittleness index and scratch recovery. 40 Although wear resistance may improve by adding silicate layers to nylon 6, this has been associated with an increase in brittle modes of deformation such as the formation of brittle cracks during scratching.…”
Section: Indentation Creep Analysismentioning
confidence: 99%
“…37 The tribology and wear of polymers and polymer-based composites is complicated by viscoelastic recovery and brittleness, [38][39][40] with Brostow and co-workers reporting a direct correlation between a brittleness index and scratch recovery. 40 Although wear resistance may improve by adding silicate layers to nylon 6, this has been associated with an increase in brittle modes of deformation such as the formation of brittle cracks during scratching. 41 A reduction in H/E when compared to matrix polymers has been reported previously for nylon 6 with 3-5% organoclay and for PEO with 7-15% and semi-crystalline polymers have shown that minimum values of the time constant 1/B are observed close to the glass transition region.…”
Section: Indentation Creep Analysismentioning
confidence: 99%